TEACHER- STUDENTS EDUCATIONAL COMMUNICATION: A DESCRIPTIVE STUDY IN MIN 2 BANJAR - Risa Dwi Ayuni; Noor Afifah; Junaidy Junaidy; Rizki Apriliyanti (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
Communication is an important aspect that involves interaction between teachers and students in the hope that the message will be well received and have an impact on understanding and changes in behavior. This research aims to analyze teacher-student communication in the educational process at MIN 2 Banjar. The method used is descriptive qualitative with interviews, observation and documentation. The result shows that communication in teaching and learning activities at MIN 2 Banjar very effective with approach of epistemological, axiological, and ontologically. The second, the Laswell Model is widely used in communication process that which can flexibly change from group communication to interpersonal communication; The third, educational communication is also effective because of the teacher play varied roles like speaker, moderator, mentor, and manager.